Learning to Hire? Hiring as a Dynamic Experiential Learning Process in an Online Market for Contract Labor - Leung, Ming D. (Management Science, 2018)
We know a job applicant’s social category affects an employer’s likelihood of hiring the applicant, but we do not know whether, or how, employers update their beliefs regarding these social categories. I portray hiring as a cognitive decision and examine how prior negative and positive hiring experiences of employees from particular countries affect an employer’s subsequent likelihood of hiring applicants from those countries. I hypothesize that employer reactions will reflect loss aversion—that employers will react more strongly to negative hiring experiences than positive ones. Furthermore, I expect that the similarity of the prior job will moderate this effect. Analyses of 3.9 million applications, from freelancers worldwide, for over 290,000 jobs on an online labor market demonstrate that employers are 15% less likely (versus 8% more likely) to hire freelancers from a country following a prior negative (versus positive) experience. Prior negative experiences with similar jobs (versus dissimilar jobs) lead employers to be 82% less likely (versus 8% less likely) to hire from that country. Conversely, positive experiences with similar jobs (versus dissimilar jobs) lead employers to be 25% more likely (versus 3% more likely) to subsequently hire from that country. The consequences for switching countries, following negative experiences, are analyzed and wage differences to compensate for employer reactions, are calculated. Contributions to the hiring discrimination, impression formation, and gig-economy literatures are discussed. This paper was accepted by Olav Sorenson, organizations.